Charging method of micro heat pipe for high‐power light‐emitting diode. (1st October 2015) - Li, Congming; Luo, Yi; Zhou, Chuanpeng; Shan, Qing; Wang, Xiaodong
Abstract : Since high precision of working fluid charging is key to the evaluation of thermal performance, a novel perfusion method of a micro heat pipe (MHP) is presented. The MHP has a length of 26 mm, width of 20 mm and a thickness of ∼2.2 mm. The predetermined quantity of perfusion is 25 or 35 μl. Small volume and large capillary force render conventional vacuum perfusion methods quite impractical. To realise microscale and high precision of perfusion, the method of combining vacuum perfusion using a peristaltic pump and weight comparison before and after working fluid charging was used. The charging deviation of the method was <2 μl. After perfusion and sealing, the thermal performance testing of a MHP, which is engineered in light‐emitting diode (LED) heat dissipation, was conducted and the input power varied from 1 to 7 W. The results show that high‐power LEDs can reach the status of heat balance and can work steadily, and the maximum deviations of actual and simulated temperatures are 4.5 and 5.1°C, respectively, and the relative errors are 6.1 and 7.3%. Therefore, this perfusion method can be used for the working fluid perfusion of the MHP and makes it feasible for use in packaging manufacture of heat pipes.